1. The problem statement, all variables and given/known data Solve: y'' - λy = 0 where y(0)=y(1)=0, y=y(t) 2. Relevant equations 3. The attempt at a solution Hi everyone, This is part of a PDE question, I just need to solve this particular ODE. I know how to do it in the case for y'' + λy = 0, where you get the solution: λ = (nπ)^2, y = C.sin(nπt), C a constant However, I don't know how to go about doing it for this case, other than getting the trivial zero solution of course. Am I correct in thinking I should rewrite it as: y'' + (-λ)y = 0 and then solve as for the positive case? I would be really grateful if you could please tell me if this is correct.